2020
DOI: 10.1186/s13293-020-00301-y
|View full text |Cite
|
Sign up to set email alerts
|

The impact of sex and gender on immunotherapy outcomes

Abstract: Immunotherapies are often used for the treatment, remission, and possible cure of autoimmune diseases, infectious diseases, and cancers. Empirical evidence illustrates that females and males differ in outcomes following the use of biologics for the treatment of autoimmune diseases, e.g., rheumatoid arthritis (RA), infectious diseases, e.g., influenza, and solid tumor cancers. Females tend to experience more adverse reactions than males following the use of a class of biologics referred to as immunotherapies. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
110
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 139 publications
(125 citation statements)
references
References 83 publications
(103 reference statements)
2
110
1
3
Order By: Relevance
“…Using a mouse model of SARS-CoV infection, Channappanavar et al showed that male mice are more susceptible to SARS-CoV infection than female mice. The enhanced susceptibility of male mice to SARS-CoV correlated with a moderate increase in virus titer and extensive inflammatory monocyte macrophages and neutrophil accumulation in the lungs [87].…”
Section: Sex-related Issues In Elderly Covid-19 Patientsmentioning
confidence: 94%
“…Using a mouse model of SARS-CoV infection, Channappanavar et al showed that male mice are more susceptible to SARS-CoV infection than female mice. The enhanced susceptibility of male mice to SARS-CoV correlated with a moderate increase in virus titer and extensive inflammatory monocyte macrophages and neutrophil accumulation in the lungs [87].…”
Section: Sex-related Issues In Elderly Covid-19 Patientsmentioning
confidence: 94%
“…Furthermore, worst might be the expected risks of severe symptomatic adverse effects experienced by women after immunotherapy due to their stronger immune responses [213,214]. Nonetheless, because of the short follow up of immunotherapy, some discrepancy still exist in regard to this point [215].…”
Section: Sex Differences and Response To Therapiesmentioning
confidence: 99%
“…Social differences can serve as disease and treatment modifiers [ 48 ]. Many drug interactions are previously acknowledged to be different in sociological variables [ 49 ].…”
Section: Roles Of Sociological Factors and Sex/gender In Cpi Efficmentioning
confidence: 99%